2014
DOI: 10.7150/ijms.7643
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lactate Dehydrogenase Levels as a Predictive Marker of Oxaliplatin-Induced Hypersensitivity Reactions in Japanese Patients with Advanced Colorectal Cancer

Abstract: Objective: Clinical laboratory test data obtained prior to treatments were previously analyzed from the standpoint of susceptibility to hypersensitivity reactions in patients treated with the platimun anticancer agent, oxaliplatin (L-OHP). In the present study, the time course from the first to last cycle of the treatment was additionally analyzed to determine a better predictor of these reactions.Methods: A total of 20 laboratory test data were obtained from 108 Japanese patients with advanced colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Additionally it has been shown that serum LDH levels could be also valuable to predict hypersensitivity reactions in colorectal cancer patients treated with the platinum anticancer agent, oxaliplatin (L-OHP) (99). In addition, Koukourakis et al reported that tissue LDHA was associated with resistance to standard chemotherapy, poor progression-free survival and high performance status in patients with advanced colorectal cancer (CRC) (100).…”
Section: Ldh As Diagnostic Marker Prognostic Factor and Predictive Mmentioning
confidence: 99%
“…Additionally it has been shown that serum LDH levels could be also valuable to predict hypersensitivity reactions in colorectal cancer patients treated with the platinum anticancer agent, oxaliplatin (L-OHP) (99). In addition, Koukourakis et al reported that tissue LDHA was associated with resistance to standard chemotherapy, poor progression-free survival and high performance status in patients with advanced colorectal cancer (CRC) (100).…”
Section: Ldh As Diagnostic Marker Prognostic Factor and Predictive Mmentioning
confidence: 99%
“…In Japan, one study revealed that serum lactate dehydrogenase (LDH) levels at the beginning of chemotherapy might predict IHSRs to oxaliplatin [20], and a Korean study suggested that the amount of dexamethasone used as premedication could predict IHSRs [21]. Further studies, however, are needed to confirm the reliability of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Normally LDH exists in almost all cytoplasm, it plays an important role in producing cell energe including cancer cells. (Seki et al, 2014). LDH can't be released into the extracellular through the cell membrance, but, this cytosolic enzyme can be released if the cell was injuried or dead.…”
Section: Discussionmentioning
confidence: 99%